Editorial - Mertens, Piet; Simon, Anne Catherine (Journal of Speech Sciences, 2021)
This issue of JoSS contains extended versions of a small selection of papers presented at the Prosody-Discourse Interface conference (Interface Discours-Prosodie, IDP), held in Leuven (Belgium), from 11 to 13 September 2013. This conference is the fifth edition in a series of biannual conferences previously held in Aix-en-Provence (2005), Geneva (2007), Paris (2009), and Salford (2011). The general topic of these conferences is the relation between prosody and discourse.